Slovenian military path to the Alliance - Šteiner, Alojz (Anali PAZU HD, 2022)
In 2019, while the North Atlantic Treaty Organization (NATO) was celebrating the 70th anniversary of its existence, Slovenia was celebrating the 15th anniversary of membership of it. Two more anniversaries must also be highlighted: namely the 25th anniversary of the beginning of international military cooperation by the Slovenian Armed Forces, and the 10th anniversary of the adoption of the declaration on the fulfilment of the conditions for the army to be fully integrated into the Alliance. In addition, the Slovenian military path to the Alliance has several other interesting facts and special features that are presented in this article on a basis of research. These include the relatively short transition from the army consisting solely of a military reserve and later a conscript army, to a professional army with a voluntary reserve; the accelerated and incomplete process of functional professionalization; and the successful integration into NATO, followed by rather irresponsible abandonment of the commitments given in defence strategic documents and to the Alliance with regard to financial investments and capability building. I highlight key positive achievements and examples of derogations and objectives not achieved in the debate.